THE EFFECT OF EDUCATION, HEALTH, UNEMPLOYMENT AND INFRASTRUCTURE ON POVERTY IN BENGKAYANG REGENCY - Deffrinica Deffrinica (Management and Sustainable Development Journal, 2019)
Education (X1) shows the results of the analysis of poverty (Y) in Bengkayang Regency. Not significant when viewed from the results of the t test partially can be obtained to count to the value of the Education Sector, -1.449> 1.796 so that education has a positive and not significant effect on poverty, which is supported by a significant level of 0.385 <0.050. This shows that the Education Sector variable has no significant effect on Poverty (Y). Health (X2) has a negative and significant effect on Poverty, which is supported by the Probability Value (sig) of 0.437 <0.050. This means that in terms of health, the government in this case has made every possible effort for budget expenditures , but in fact in the field there are still many underprivileged people who have not been able to enjoy maximum hospital services. The results of the analysis of the direct effect of Unemployment (X3) on Poverty in Bengkayang Regency showed insignificant influence. The results of the analysis show that this path has a significant effect because the value of t count is 1,217, while the table is 1,796 (t count 1,217> t table 1,796), thus in this direct relationship pattern, unemployment has a positive effect not significant to poverty, which is supported by Probability Value (sig) 0.371> 0.050. The results of the analysis of direct influence of Infrastructure (X4) on poverty levels in Bengkayang Regency show that the path coefficient between Infrastructure and poverty is 0.804> 0.050, which means that the pathway has a negative and insignificant effect. The method used to analyze this research is linear regression with the least squares method usually known as OLS (Ordinary Least Square), which is a method used to determine the effect of an independent variable on the dependent variable.